Трансформация концепции Эроса Платона в философско-этическом творчестве Бориса Вышеславцева - Łucenko, Jelena (Acta Polono-Ruthenica, 2006)
In the article analyzed is the essence of Eros in the conception of the Russian philosopher Boris Wyszeslawcew against the background of the New interpretation of Plato’s theory relating to Eros.